Campur Kode dalam Instagram TV "Haipuja" - Melati, Arum Sekar; Pastika, I Wayan; Arnati, Ni Wayan (Stilistika : Journal of Indonesian Language and Literature; Vol 2 No 2 (2023): Volume 2 No 2, April 2023, 2023)
The topic in this article is “Code mixing in Instagram TV “Haipuja”. The background of this research is, in the Instagram TV video "Haipuja" there is the use of code mixing in it, both the insertion of regional languages ??into the use of Indonesian and the insertion of foreign languages ??into the use of Indonesian. The research on code mixing on Instagram TV “Haipuja” has never been done before. In this study, there are three problems discussed, namely code mixing based on the origin of the absorption elements, code mixing at the linguistic level, and the factors causing code mixing. The purpose of this study is to determine the use of code mixing, as well as the factors that cause code mixing. Qualitative descriptive research is presented in the form of data descriptions. Data collection methods are supported by note-taking techniques and the results of data analysis are presented in an informal form. The results of this study were found code mixing based on the original absorption element, code mixing seen from the linguistic level, and the factors causing code mixing on Instagram TV “Haipuja”.